Biogas reforming integrated with PEM electrolysis via oxygen storage process for green hydrogen production: From design to robust optimization. (1st January 2022) - Kim, Jeongdong; Qi, Meng; Kim, Minsu; Lee, Jaewon; Lee, Inkyu; Moon, Il
Highlights: Oxygen gas produced from the PEMEC is used for biogas ATR reforming for large-scale hydrogen production. Continuous oxygen supplied is available using intermediate oxygen storage system. The LCOH of the proposed system is distributed between 4 $/kgH2 and 10 $/kgH2 under uncertainties. Robust optimization reduces mean and variance of the LCOH by 11.96 % and 37.81% on average. The proposed system could provide low LCOH in current green hydrogen market. Abstract: The oxygen gas produced from electrolysis is both a good heat supplier and an oxidizing agent for the autothermal reforming (ATR) process. Thus, green hydrogen production could be achieved by integrating the biogas ATR and electrolysis processes directly with renewable power sources. Under the natural fluctuation of renewable power, the oxygen produced from electrolysis can be stored in a compressed or liquid state in an intermittent storage tank to buffer its production rate for steady-state operation of biogas ATR process. In this study, integrated systems have been newly proposed using compressed gas and liquid oxygen storage methods, which are denoted as PEMCOAR and PEMLOAR systems, respectively. Using the surrogate model based on polynomial chaos expansion methodology (PCE), the statistical moments of levelized cost of hydrogen (LCOH) of both proposed systems were optimized considering the uncertainties of renewable power, biogas composition, and electricity tariff. As a result, the mean and variance of LCOH is reduced by 11.9% and 37.8%, respectively. In case of renewable power and biogas price of 0.06 $/kWh and 5.58 $/MMBTU, it was observed that the average LCOH below the current green hydrogen market price at a renewable power scale of over 55 MW. In conclusion, the study suggests the optimal operating condition under uncertainties and simultaneously, prove the economic feasibility of integrating electrolysis and biogas ATR systems.